Pengaruh model pembelajaran inkuiri terbimbing (guided inquiry) berbantuan video animasi terhadap kemampuan berpikir kritis matematis siswa kelas V SD - Diah Ayu Paramita; Zulmi Roestika Rini (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to determine the effect of a guided inquiry learning model assisted by animated video on students' mathematical critical thinking skills. The research method used a quantitative experiment with a Quasi-Experimental design (Non-Equivalent Control Group Design). The population in this study were all fifth-grade students of SD Negeri Kupang 01. The research sample was class VA as the experimental class while class VB was the control class. Data collection techniques with test techniques through pretest and posttest and non-test techniques include observation, documentation, unstructured interviews, and questionnaires. Data analysis was conducted using a normality test, homogeneity test, independent sample t-test, and simple linear regression test. The results showed: There is an effect of the guided inquiry learning model assisted by animated video on students' mathematical critical thinking skills, with the results of a simple linear regression test showing a significant value of 0.000 <0.05.